Poisson stability in product of dynamical systems - A. Kumar; R. P. Bhagat (International Journal of Mathematics and Mathematical Sciences)
This paper deals with Poisson stable and distal dynamical system. It is shown that the product of Poisson stable motions is a Poisson stable motion in dynamical systems.